Mapping of Degraded Soil Properties in Gunung Leuser National Park - Deni Elfiati; Asnur, Paranita; Siddik Thoha, Achmad (Journal of Sylva Indonesiana, 2019)
Deforestation that occurs causes a decrease in soil fertility. Knowing soil fertility in the landscape will provide information on land management. The nature of the soil differs from one point to another, therefore it is necessary to map the properties of the soil. The purpose of this study is to map the distribution of the properties of forest land in areas that have been degraded. The land is a former privately-owned oil palm plantation in the Gunung Leuser National Park (TNGL) forest. The study uses a continuous grid interpolation method, thus forming polygons of soil properties. The soil types are Inseptisol an Ultisol. The results of the study show that most of them belong to the type of soil that is finely textured so that erosion can easily occur if surface runoff occurs in areas that have been exposed. The soil water content range that has the widest area is the range 26.98 - 29.50% with an area of 14.38 ha (42.91% of the research area). The range of land capacity has the widest area, namely the range 42.24 - 49.32% with an area of 13.32 ha (39.76% of the research area). Low organic matter content and acidic soil pH. Based on the results of these studies, the land in the research area is less fertile. However, restoration efforts are very possible because many tree species are adaptive with low soil fertility.